Resistance and virulence features of hypermucoviscous Klebsiella pneumoniae from bloodstream infections: Results of a nationwide Italian surveillance study - Arena, Fabio; Menchinelli, Giulia; Di Pilato, Vincenzo; Torelli, Riccardo; Antonelli, Alberto; Henrici De Angelis, Lucia; Coppi, Marco; Sanguinetti, Maurizio; Rossolini, Gian Maria (Frontiers in Microbiology, 2022)
Among Enterobacterales, Klebsiella pneumoniae (Kp) is one of the major opportunistic pathogens causing hospital-acquired infections. The most problematic phenomenon linked to Kp is related to the dissemination of multi-drug resistant (MDR) clones producing carbapenem-hydrolyzing enzymes, representing a clinical and public health threat at a global scale. Over the past decades, high-risk MDR clones (e.g., ST512, ST307, ST101 producing blaKPC–type carbepenemases) have become endemic in several countries, including Italy. Concurrently, the spread of highly virulent Kp lineages (e.g., ST23, ST86) able to cause severe, community-acquired, pyogenic infections with metastatic dissemination in immunocompetent subjects has started to be documented. These clones, designated as hypervirulent Kp (hvKp), produce an extensive array of virulence factors and are highly virulent in previously validated animal models. While the prevalence and distribution of MDR Kp has been previously assessed at local and national level knowledge about dissemination of hvKp remains scarce. In this work, we studied the phenotypic and genotypic features of hypermucoviscous (HMV, as possible marker of increased virulence) Kp isolates from bloodstream infections (BSI), obtained in 2016–17 from 43 Italian Laboratories. Antimicrobial susceptibility testing, whole genome sequencing and the use of two animal models (G. mellonella and murine) were employed to characterize collected isolates. Over 1502 BSI recorded in the study period, a total of 19 Kp were selected for further investigation based on their HMV phenotype. Results showed that hvKp isolates (ST5, ST8, ST11, ST25) are circulating in Italy, although with a low prevalence and in absence of a clonal expansion; convergence of virulence (yersiniabactin and/or salmochelin, aerobactin, regulators of mucoid phenotype) and antimicrobial-resistance (extended-spectrum beta-lactamases) features was observed in some cases. Conventional MDR Kp clones (ST307, ST512) may exhibit an HMV phenotype, but with a low virulence potential in the animal models. To the best of our knowledge, this work represents the first systematic survey on HMV and hvKp in Italy, employing a functional characterization of collected isolates. Future surveillance programs are warranted to monitor the threatening convergence of virulence and resistance among MDR Kp and the spread of hvKp.